Silvia Lupo (ed.), Tell el-Ghaba III. A Third Intermediate-Early Saite Period Site in the Egyptian Eastern Delta. Excavations 1995–1999 and 2010 in areas I, II, VI and VIII. BAR International Series 2756. Oxford, Archaeopress. 2015, 437 pp. ISBN-13: 978-1407314174 - Defernez, Catherine (2019)
Fil: Defernez, Catherine. Centro Nacional Francés de Investigación Científica; Francia